Discipline Character of Students in the Modern Era Synergy of Parents and Teachers in State Islamic Junior High School in Klaten Regency - Hartini, Sri (Institut Agama Islam Negeri (IAIN) Tulungagung, 2018)
Character education is currently being intensely promoted in the formal education specifically. At this time various moral crises and problems arise in society. Corruption is everywhere, crime is rampant, and thuggery becomes the solution. In the government bureaucracy, most of the state institutions are not clean from the cases of corruption, violence against students, sexual abuse of students, fraudulent acts, lying, brawls between students, western love culture, free sex, and the use of drug. So, that is the background that character education is needed to be carried out. This study aims to describe the values ​​of embedded character education and describe the disciplinary character education of students in the modern era why it takes a synergy between parents and teachers in the State Islamic Junior High School in Klaten Regency. The findings of this study indicate that the character values ​​embedded in State Islamic Junior High School in Klaten Regency have some similarities and differences, the implementation of character education is carried out through four dimensions, namely learning activities, religious activities, extracurricular and co-curricular and the building of madrasa culture. Discipline character education of students of the modern era need a synergy between parents and teachers, because of lots of parents' activities, the parents no longer have time for children. Cooperation between parents and teachers to achieve the goals in the education process is very important.